PENGARUH TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BEI 2018-2021 - Nurmalina, Rina; Ruhana, Nafisah (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2024)
The value of the company, which is indicated by the share price, is one of the factors considered by investors when investing in the company. The higher the share price, the higher the profit value that investors will receive. One way that companies increase company value is by practicing tax avoidance. When a company is able to minimize tax payments, the company is able to maintain its profits, this is a positive signal for investors. So the aim of this research is to prove empirically whether there is a connection between tax avoidance practices that occur in various industrial sector manufacturing companies and company value. The research was carried out using a quantitative approach, where the author will test the influence of the independent variable, namely Tax Avoidance, on the dependent variable, namely company value, which is proxied by Price to Book Value (PBV). The research population is Manufacturing Companies in the Various Industrial Sector spanning 2018-2021, while the research sample consists of 29 companies. The research results show that tax avoidance has a positive but not significant effect.